תשובה:
ראה תהליך פתרון בהמשך:
הסבר:
למצוא #p (2) # תחליף #color (אדום) (2) # עבור כל התרחשות של #color (אדום) (x) # בפונקציה #p (x) # ולחשב את התוצאה:
# צבע (אדום) (x) = צבע (אדום) (אדום) (x) + 4 + 3 צבע (אדום) (x) ^ 3 - 6 צבע (אדום) (x) ^ 2 - 8 צבע (אדום) (x) הופ post
# צבע (אדום) (2)) = צבע (אדום) (2) ^ 4 + (3 * צבע (אדום) (2) ^ 3) - (6 * צבע (אדום) (2) ^ 2) (8 * צבע (אדום) (2)) #
# # (צבע) (אדום) (2)) = 16 + (3 * 8) - (6 * 4) - 16 #
#p (צבע (אדום) (2)) = 16 + 24 - 24 - 16 #
#p (צבע (אדום) (2)) = 0 #